KARAKTER MASYARAKAT INVESTOR KOTA PALEMBANG - MOHAMAD ADAM (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2015)
The purpose of this study is to determine the character of the investor community Palembang. The type of data in this study is qualitative data. This means that the data is obtained in the form of views and opinions of the source namely investors who trade in securities office. This study uses the tools in the form of a list of questions (questionnaire). There are four types of characters Palembang investor community that is high risk taker, medium risk taker, low risk taker, and full risk averser. Based on the results of research, investor community character of Palembang is a medium risk taker as many as 77%, while the remaining 13% are low risk takers, and 10% is a high risk taker.